A omissão do mal em It – A Novel - Melo, Michel Miron de (2023)
This dissertation investigates the ways that the monster of the It - A Novel shapes the evil in the citizens of the fictional city of the novel. Realizing that the "It", while a monster, holds layers of potential damage way deeper and invisible that the killings that it commits. This work argues that the monster can work as a metaphor for omitted acts of violence, present, in this case, in the North American past and present, full of racism and imperialism. This is demonstrated in the worry that the object of study has with the history of the country. Another objective of this dissertation it's to argue that the book has the identity as its main theme while showing that the seven protagonists, no matter de chronological order, are building their identities or searching them on their lost memories, always to survive and defeat It who, by possessing technically infinite identities, is a monster that holds none, possesses a root identity that can never be fully comprehended by the man. This multifaceted identity of the monster is an argument to say that It - A Novel (1986) is a post-modernist novel, as seen in Hutcheon (2003), Hall (1996), and Jameson (1997) This point of the monster as a metaphor basis in the arguments and perceptions of Arendt (2006) about a terrible but banal evil, showing that It can represent the potential of even the most common of man to be able to do the most heinous acts. It shows the capacity of a society to omit the existence of terrible episodes of the past or present and to keep growing under late capitalism.